Virtual inertia support for wind turbine system - Nor Shahida Hasan; Norzanah Rosmin; Nor Julia Mohd Nordin; Aede Hatib Mustaamal; Siti Maherah Husin; Aripriharta Aripriharta; Ira Devi Sara (Institute of Advanced Engineering and Science, 2020)
Previously, a conventional synchronous generator is adapted into the wind energy conversion system to supply the required inertial support; however its slow behaviour may worsening the stability problem of the system during frequency event. In this paper, a new approach that enables virtual inertial support from supercapacitor during sudden load increase e.g. when wind turbine experiencing sudden wind or load changes is presented. Here, a new approach that can regulate the system frequency by controlling the charging and discharging process of supercapacitor is demonstrated. Hence, an algorithm on how to derive the behavior of supercapacitor and power converter is presented. From the simulation results, it has been found that this proposed approach successfully reduces the frequency nadir and ROCOF of the system frequency. It also able to avoid the second frequency dips during frequency recovery time.